Reversing Racism in the Time of Reconciliation? Settler Colonialism, Race, and Alberta Teachers - Danielle Lorenz (Canadian Society for Studies in Education, 2017)
With Alberta Education planning new policies and curricula that focus on Indigenous content, it is important to see how educators recognize and explain racism. This quanti-qualitative study examines the ways in which Alberta Teachers' Association (ATA) members understand and articulate racism through their responses to an anonymous online survey. This is investigated through an interrogation of the idea of "reverse racism." Utilizing settler colonialism as a theoretical framework, this article uses the history of race as a concept and an exploration of terms related to racism to refute the possibility of white people experiencing racism in Canada. The article concludes that settler colonialism and racism are coexisting and oppressive systems that prohibit reconciliatory thinking for settlers.